Predictive Role of Blood Cellular Indices and Their Relationship with Endogenous Glycosaminoglycans as Determinants of Inflammatory Biomarkers in Pulmonary Embolism. (June 2022) - Kantarcioglu, Bulent; Darki, Amir; Siddiqui, Fakiha; Krupa, Emily; Vural, Mehmet; Kacmaz, Murat; Hoppensteadt, Debra; Iqbal, Omer; Jeske, Walter; Walenga, Jeanine; Adiguzel, Cafer; Fareed, Jawed
Introduction: In this study, we profiled the levels of blood cellular indices, endogenous glycosaminoglycans (GAGs) and inflammatory biomarkers in a cohort comprised of pulmonary embolism (PE) patients, to determine their inter-relationships. Identification of this relationship may provide insight to the complex pathophysiology of PE and the predictive role of blood cellular indices in acute PE patients. Materials and Methods: Plasma samples from PE patients and healthy controls were analyzed for thrombo-inflammatory biomarkers (IL-2, IL-4, IL-6, IL-8, IL-10, VEGF, IFN-ɣ, TNF-α, IL-1α, IL-1β, MCP-1, EGF, D-dimer, CRP and MMP-9) using biochip array and ELISA methods. The endogenous GAG levels were quantified using a fluorescence quenching method. The data regarding the blood cellular indices were collected through the review of patient medical records and analyzed to demonstrate their relationship. Results: The levels of inflammatory biomarkers and endogenous GAGs were elevated in acute PE patients compared to controls ( P < .05). Most of the blood cellular indices have shown significant differences in acute PE patients compared to controls ( P < .05). The levels of inflammatory biomarkers, endogenous GAGs and the blood cellular indices have shown significant associations in correlation and multivariable analysis. While NLR, PLR and SII were significantly predicting the 30-day mortality, PNR, ELR and EMR were not sufficient to predict 30-day mortality in acute PE. Conclusion: Our results show that the increased thrombo-inflammatory response is associated with the release of GAGs and the changes in blood cellular indices. The predictive role of the blood cellular indices for mortality is dependent on their relationship with the inflammatory response.